2014
DOI: 10.1093/cercor/bhu199
|View full text |Cite
|
Sign up to set email alerts
|

The Default Mode Network Differentiates Biological From Non-Biological Motion

Abstract: The default mode network (DMN) has been implicated in an array of social-cognitive functions, including self-referential processing, theory of mind, and mentalizing. Yet, the properties of the external stimuli that elicit DMN activity in relation to these domains remain unknown. Previous studies suggested that motion kinematics is utilized by the brain for social-cognitive processing. Here, we used functional MRI to examine whether the DMN is sensitive to parametric manipulations of observed motion kinematics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 90 publications
2
16
0
1
Order By: Relevance
“…As shown in Figure a ( inset ), the deactivated regions, which were localized to the vmPFC, posterior cingulate gyrus, and precuneus, corresponded closely to a published DMN pattern identified using resting‐state fMRI scan data (Wang et al, ). The close covariance relationship of these regions to the subspace of activated VPRP nodes is consistent with recent findings implicating the DMN in the perception of biological motion (Dayan et al, ). The degree to which the deficits in VPRP modulation seen in dystonia are a consequence of inherent DMN pathology is not known.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure a ( inset ), the deactivated regions, which were localized to the vmPFC, posterior cingulate gyrus, and precuneus, corresponded closely to a published DMN pattern identified using resting‐state fMRI scan data (Wang et al, ). The close covariance relationship of these regions to the subspace of activated VPRP nodes is consistent with recent findings implicating the DMN in the perception of biological motion (Dayan et al, ). The degree to which the deficits in VPRP modulation seen in dystonia are a consequence of inherent DMN pathology is not known.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent report, biological motion perception was linked to the default mode network (DMN) (Dayan et al, ). We therefore used voxel‐based correlation analysis (Ko, Spetsieris, Ma, Dhawan, & Eidelberg, ) to evaluate the topographic relationship between the VPRP and a probabilistic DMN template described previously using resting‐state fMRI and independent component analysis (ICA) (Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Accurate perception of biological motion requires individuals to first track motion timings, then integrate perceived timings into a coherent kinematic framework for higher-order processing. Consistent with this notion, previous research showed that DMN deactivation was necessary for healthy adults in order to process biological motion [41]. …”
Section: Introductionsupporting
confidence: 58%
“…It is yet unclear how these different forms of safety learning are related to each other and more research is necessary to address this question. Based on our results, we suggest that the DMN might constitute a high‐level form of safety learning that integrates other cognitive functions involved in threat and safety processing, such as perception, attention, cognitive inhibition, and higher‐order reasoning, as well as working and long‐term memory [Anderson et al, ; Dayan et al, ; Elton and Gao, ]. The DMN's functional profile, the rich‐club properties of its hub regions (especially the medial prefrontal and medial temporal cortices), as well as its effective, global structural connectivity make it well suited for such an integrated, contextual form of safety learning [Van den Heuvel and Sporns, ; Vatansever et al, ].…”
Section: Discussionmentioning
confidence: 80%